U–Pb geochronology, isotope systematics, and geochemical characteristics of the Triassic Dasuji porphyry Mo deposit, Inner Mongolia, North China: Implications for tectonic evolution and constraints on the origin of ore-related granitoids. (1st October 2018) - Wu, Huaying; Zhang, Lianchang; Gao, Jun; Zhang, Min; Zhu, Mingtian; Xiang, Peng
Graphical abstract: Highlights: The granite-porphyry-hosted Dasuji Mo deposit was emplaced at ∼224 Ma. Mo mineralization in the Dasuji deposit occurred at ∼223 to 224 Ma. The porphyry granitoids were derived from partial melting of old lower crust. Late Triassic Mo mineralization is related to post-collisional regional extension. Abstract: The Dasuji porphyry Mo deposit is located in the Wulanchabu area of Inner Mongolia, within the northern North China Craton (NCC). Three phases of Mesozoic felsic intrusions have been recognized in the mining area, including two pre-mineralization intrusions (i.e., a quartz porphyry and a granite porphyry) with molybdenite-bearing stockworks and veins, and an ore-related granite porphyry with disseminated and stockwork Mo mineralization. Zircon U–Pb–Hf analyses, intergrated with the previously reported molybdenite Re–Os isochron ages, suggest that the Mo mineralization of the Dasuji deposit occurred in the Late Triassic (222–224 Ma) and that the ore-related granitoids were derived from partial melting of old lower crust, with a subordinate contribution from mantle materials. Major and trace element analyses show that the pre-ore granite porphyry (227 Ma) and the ore-related granite porphyry (224 Ma) are both characterized by high silica contents and relatively high levels of oxidation, with a high differentiation index (DI = 85.0–98.8). The granitoids belong to the high-K calc-alkaline series and are highly peraluminous, with depletion in Ba, Sr, P, Eu, and Ti, showing similar geochemical characteristics to those of post-collision-related granitoids in North China. Based on geological, geochronological, isotope systematic, and geochemical studies, integrated with regional geological information, we suggest that the Dasuji Mo deposit was formed in a post-collisional setting associated with the transition from regional compression to extension between the NCC and the Central Asian Orogenic Belt (CAOB) during the Late Triassic.